Proton Conductive Materials
Sulfuric acid-modified metal oxides with optimized pore structure enhance proton conductivity durability by using sulfuric acid-supported metal oxides in electrochemical devices.
Patent Information
- Application Number
- JP2021176422
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-28
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-10-28
AI Technical Summary
Nafion, a polymeric proton conductive material, experiences a decrease in proton conductivity over time due to its low durability.
A proton conductive material composed of sulfuric acid-modified metal oxides, such as TiO2, SnO2, ZrO2, or WO3, with sulfuric acid supported on the surface, and a pore structure optimized for proton conduction, specifically with a high volume of pores ≤5 nm, enhancing durability.
The material effectively suppresses the decrease in proton conductivity, maintaining high conductivity over extended periods by utilizing capillary condensation in small pores.
Smart Images

Figure 0007602991000002 
Figure 0007602991000003 
Figure 0007602991000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a proton conducting material. [Background technology]
[0002] Proton-conducting materials are widely used in electrochemical devices such as fuel cells, electrolysis cells, electrochromic display devices, and sensors.
[0003] 2. Description of the Related Art Conventionally, a solid polymer material made of Nafion (registered trademark, manufactured by DuPont), which is a perfluorosulfonic acid ion exchange polymer, has been known as a proton conductive material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-036360 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, since Nafion is a polymer material and has low durability, its proton conductivity is likely to decrease with long-term use.
[0006] An object of the present invention is to provide a proton-conductive material capable of suppressing a decrease in proton conductivity. [Means for solving the problem]
[0007] The proton conductive material according to the present invention is composed of a plurality of sulfate-modified metal oxide particles each having a metal oxide containing at least one of Ti, Sn, Zr, and W, and sulfuric acid supported on the surface of the metal oxide. In a pore size distribution curve obtained by a nitrogen adsorption method, the volume of pores having a pore size of 5 nm or less is 0.040 cm. 3 / g or more. Effect of the Invention
[0008] According to the present invention, it is possible to provide a proton conductive material capable of suppressing a decrease in proton conductivity. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic diagram of sulfate-modified metal oxide particles constituting a proton-conductive material. [Diagram 2] FIG. 2 is a schematic diagram showing the structure of the surface of a sulfate-modified metal oxide particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Composition of proton conductive materials) The proton conductive material according to this embodiment can be used as a constituent material of a proton conductive membrane in electrochemical elements such as fuel cells, electrolysis cells, electrochromic display elements, and sensors.
[0011] Fig. 1 is a schematic diagram of a sulfuric acid-modified metal oxide particle 10 constituting a proton conductive material, and Fig. 2 is a schematic diagram showing the structure of the surface of the sulfuric acid-modified metal oxide particle 10.
[0012] The proton conductive material is composed of a plurality of sulfate-modified metal oxide particles 10. Each sulfate-modified metal oxide particle 10 may be a single crystal composed of one crystallite, but is typically a polycrystalline body composed of a plurality of crystallites.
[0013] The sulfuric acid modified metal oxide particle 10 has a metal oxide 20 as a carrier and a plurality of sulfuric acids 30 supported on the metal oxide 20. FIG. 2 illustrates a state in which the sulfuric acid 30 is supported on the surface of the metal oxide 20. In FIG. 2, TiO2 is exemplified as the metal oxide 20, and a sulfonyl group is exemplified as the sulfuric acid 30. In this specification, "supported" means a state in which a substance is chemically bonded to the surface of the carrier. The sulfuric acid 30 supported on the surface of the metal oxide 20 does not flow out into the water even when the proton conductive material is immersed in water (for example, at 60° C. for 3 hours).
[0014] The metal oxide 20 contains at least one of Ti, Sn, Zr, and W. The metal oxide 20 is a strong acid ( pH It is preferable that the elution does not occur at a temperature below 3°C.
[0015] Examples of the metal oxide 20 include, but are not limited to, TiO2 (titania), SnO2 (tin dioxide), SnO (tin oxide), ZrO2 (zirconia), ZrSiO4 (zircon), Zr(WO4)2 (zirconium tungstate), WO3 (tungsten oxide), and Al2(WO4)3 (aluminum tungstate).
[0016] The proton-conducting material may be composed of two or more types of sulfate-modified metal oxide particles 10 containing different metal oxides.
[0017] Sulfuric acid 30 is supported on the surface of the metal oxide 20. Examples of sulfuric acid 30 include, but are not limited to, H2SO4 and its compounds, SO, S2O3, SO2, SO3, S2O7, SO4, compounds containing these sulfur oxides (acids, salts, etc.), and mixtures of these.
[0018] The molar ratio (S / M) of sulfur (S) in the sulfuric acid content in the sulfuric acid 30 to the metal element (M) in the metal oxide 20 can be set to 0.01 or more and 0.2 or less.
[0019] In this embodiment, the proton conductive material is composed of a plurality of sulfate-modified metal oxide particles 10 and has a plurality of sulfuric acids 30 supported on the metal oxide 20, but may further have unsupported sulfuric acid that is not supported on the metal oxide 20. The unsupported sulfuric acid may be in contact with the surface of the metal oxide 20 or may be separated from the surface of the metal oxide 20. The unsupported sulfuric acid flows out into the water when the proton conductive material is immersed in water (e.g., at 60°C for 3 hours).
[0020] The presence of sulfuric acid 30 in a proton conductive material can be confirmed by the following method. First, the total amount of sulfuric acid contained in 1 g of the proton conductive material is measured by ICP analysis of a solution containing 1 g of the proton conductive material. Next, the content of unsupported sulfuric acid contained in 1 g of the proton conductive material is calculated, and the content of sulfuric acid 30 is calculated by subtracting the content of unsupported sulfuric acid from the total amount of sulfuric acid. If the calculated content of sulfuric acid 30 is greater than 0, it can be said that the proton conductive material contains sulfuric acid 30.
[0021] The content of unsupported sulfuric acid can be measured by the following method. First, a mixture of 100 mL of deionized water and 1 g of proton conductive material is heated in a water bath heated to 60°C for 3 hours. Next, the total weight of the heated mixture is measured, and the amount of deionized water remaining without evaporation is calculated. Next, the mixture is centrifuged to precipitate solid components, and the supernatant is collected and subjected to ICP analysis to measure the sulfuric acid content in the supernatant. Next, the content of unsupported sulfuric acid is calculated based on the amount of deionized water remaining without evaporation and the sulfuric acid content in the supernatant.
[0022] (Proton Conductive Material Characteristics) 1. Pore volume Proton-conducting materials have many pores. The volume of pores with a diameter of 5 nm or less in proton-conducting materials is 0.040 cm 3 / g or more. This allows the moisture required for proton conduction to be taken in by utilizing the capillary condensation phenomenon in fine pores with a pore diameter of 5 nm or less, thereby preventing the proton conductivity of the proton-conducting material from decreasing.
[0023] The volume of a pore with a diameter of 5 nm or less is 0.056 cm 3 / g or more is preferable. This makes it possible to further suppress the decrease in proton conductivity. Note that there is no particular upper limit on the volume of pores having a pore diameter of 5 nm or less.
[0024] The volume of pores with a pore diameter of 5 nm or less is measured based on the adsorption isotherm obtained by the nitrogen adsorption method as follows. First, a dried proton conductive material is placed in a measurement cell as a sample, and a vacuum degassing process is performed at 130°C for about 5 hours. Next, using a Microtrack Bell BELSORP18PLUS-HT, the sample is kept at liquid nitrogen temperature in a gas flow of 100% nitrogen by volume, and nitrogen is adsorbed onto the sample to obtain a nitrogen adsorption isotherm. Next, a pore size distribution curve of the sample is obtained by the BJH (Barret-Joyner-Halenda) method using this adsorption isotherm. The volume of pores with a pore diameter of 5 nm or less is then calculated from the obtained pore size distribution curve.
[0025] In this specification, the pore size means the diameter of the pore.
[0026] 2.Crystallite size As described above, the sulfate-modified metal oxide particles 10 constituting the proton-conductive material contain one or more crystallites. The diameter of the crystallite (hereinafter referred to as "crystallite diameter") is not particularly limited, but can be 10 nm or less. The lower limit of the crystallite diameter is not particularly limited, but can be, for example, 2 nm or more.
[0027] The crystallite size is measured using a powder X-ray diffractometer (trade name D8 advance, manufactured by Bruker AXS) under the following conditions.
[0028] <Measurement conditions> X-ray tube...Cu X-ray output: 40 kV, 40 mA Scan speed: 0.7 seconds / 0.12°C Step width: 0.12°C Scanning range: 5~70℃ Sample rotation: 15 rpm
[0029] The diffraction pattern of the sulfate-modified metal oxide particles 10 obtained by the measurement under the above conditions is analyzed by the Fundamental Parameter method (FP method) using the analysis software TOPAS manufactured by Bruker AXS. The crystallite size can be calculated by the Single Profile Fitting method (SPF method) based on the Scherrer formula. The k value used in the calculation of the SPF method can be set to 1.0. The crystallite size is calculated for each diffraction peak of X-ray diffraction, but in this specification, the crystallite size calculated from the diffraction peak of the (101) plane is used.
[0030] (Method of manufacturing proton conductive material) Next, as an example of a method for producing a proton conductive material, a case in which TiO2 is used as the metal oxide 20 will be described.
[0031] First, an aqueous solution of TiOSO4 (titanyl sulfate) is prepared. The concentration of TiOSO4 is set to, for example, 0.4% by mass or more and 15% by mass or less.
[0032] Next, the TiOSO4 solution is heated to hydrolyze it, resulting in TiO2 particles with sulfate residues on the surface. These TiO2 particles contain a large amount of water, so they are called hydrous titanium oxide.
[0033] Next, the obtained hydrous titanium oxide is washed and then dried (40° C. to 60° C., 4 hours to 24 hours) to obtain sulfate-modified TiO2 particles.
[0034] Next, the proton-conducting material is completed by aging the sulfate-modified TiO2 particles. This aging process forms fine pores with a diameter of 5 nm or less. The mechanism by which pores with a diameter of 5 nm or less are formed by aging is unclear, but it is thought to be due to the rearrangement of crystallites that make up the sulfate-modified TiO2 particles as they grow.
[0035] Aging is performed by leaving the sulfate-modified TiO2 particles in a high-temperature and high-humidity environment at a temperature of 80°C to 90°C and a humidity of 80% RH to 98% RH for 5 to 24 hours. The aging conditions are as follows: the volume of pores with a pore diameter of 5 nm or less in the proton conductive material is 0.040 cm 3 / g or more (preferably 0.056 cm 3 / g or more).
[0036] (Modification of the embodiment) Although the embodiments of the present invention have been described above, the present invention is not limited to these, and various modifications are possible without departing from the spirit of the present invention.
[0037] In the above embodiment, the volume of pores having a pore size of 5 nm or less in the proton conductive material is reduced to 0.040 cm by aging the sulfate-modified TiO2 particles. 3 / g or more, but the volume of pores with a pore size of 5 nm or less in the proton conductive material can be reduced to 0.040 cm by calcining the sulfate-modified TiO2 particles. 3 As with aging, the mechanism by which pores with a diameter of 5 nm or less are formed by firing is unclear, but it is thought to be due to the rearrangement of crystallites that make up the sulfate-modified TiO2 particles as they grow.
[0038] The calcination is carried out in an air atmosphere at 300°C to 600°C for 0.5 to 10 hours. The calcination conditions are as follows: the volume of pores in the proton conductive material having a pore diameter of 5 nm or less is 0.040 cm 3 / g or more (preferably 0.056 cm 3 / g or more). EXAMPLES
[0039] An embodiment of the present invention will be described below. In this embodiment, the volume of pores having a pore diameter of 5 nm or less in a proton conductive material is set to 0.040 cm 3 / g or more, the effect of suppressing the decrease in proton conductivity will be verified. However, the present invention is not limited to the examples described below.
[0040] (Preparation of Samples No. 1 to 11) First, titanyl sulfate was dissolved in water to prepare a TiOSO4 aqueous solution (concentration: 3.2 mass%), which was then heated at 80° C. for 1 hour to produce hydrous titanium oxide.
[0041] Next, the hydrous titanium oxide was washed and then dried (60°C, 16 hours) to obtain sulfate-modified TiO2 particles.
[0042] In samples No. 1 and 8, the sulfate-modified TiO2 particles after drying were used as proton-conducting materials as they were. That is, in samples No. 1 and 8, the sulfate-modified TiO2 particles after drying were not subjected to aging or calcination. On the other hand, in samples No. 3, 6, and 10, the sulfate-modified TiO2 particles after drying were calcined to complete the proton-conducting materials. In samples No. 3, 6, and 10, the volume of pores with a pore diameter of 5 nm or less was changed by adjusting the calcination temperature (300°C to 600°C) and time (0.5 hours to 10 hours) as shown in Table 1. In samples No. 2, 4, 5, 7, 9, and 11, the sulfate-modified TiO2 particles after drying were aged to complete the proton-conducting materials. In samples No. 2, 4, 5, 7, 9, and 11, the volume of pores with a pore diameter of 5 nm or less was changed by adjusting the aging temperature (80°C to 90°C), humidity (80% RH to 98% RH), and time (5 hours to 24 hours), as shown in Table 1.
[0043] (Preparation of Samples No. 12 to 14) For sample No. 12, zirconium oxide chloride (ZrOCl2) was dissolved in water to prepare an aqueous solution, and ammonium hydroxide (NH4OH) was dropped into the aqueous solution to hydrolyze the powder obtained, and then sulfuric acid (1 mol / L) was dropped into the powder to perform a sulfuric acid treatment, obtaining sulfate-modified zirconia particles. For sample No. 13, sodium stannate (Na2SnO3) was dissolved in water to prepare an aqueous solution, and then sulfuric acid (1 mol / L) was dropped into the aqueous solution to hydrolyze the powder, and then hydrothermal treatment was performed at 100°C for 16 hours to obtain sulfate-modified tin particles.
[0044] For sample No. 14, sulfuric acid (1 mol / L) was added dropwise to an aqueous solution prepared by dissolving sodium tungstate (Na2WO4) in water to hydrolyze the solution, and the solution was then subjected to hydrothermal treatment at 100°C for 16 hours to obtain sulfate-modified tungsten particles.
[0045] Then, the obtained sulfate-modified zirconia particles, sulfate-modified tin particles, and sulfate-modified tungsten particles were aged to complete proton-conductive materials according to Samples No. 12 to 14. In Samples No. 12 to 14, the volume of pores having a pore diameter of 5 nm or less was adjusted by adjusting the aging temperature (80°C to 90°C), humidity (80% RH to 98% RH), and time (5 hours to 24 hours) as shown in Table 1.
[0046] (Measurement of the volume of pores with a diameter of 5 nm or less) Samples of the proton conductive materials of Samples No. 1 to 14 were placed in a measurement cell and subjected to a degassing treatment under reduced pressure at 130° C. for 5 hours.
[0047] Next, using a Microtrack Bell BELSORP18PLUS-HT, the sample was kept at liquid nitrogen temperature in a gas flow of 100% by volume of nitrogen, and nitrogen was adsorbed onto the sample to obtain a nitrogen adsorption isotherm.
[0048] Next, the pore size distribution curve of the sample was obtained by the BJH method using this adsorption isotherm.
[0049] The volume of pores with a pore size of 5 nm or less was then calculated from the pore size distribution curve.
[0050] (Measurement of proton conductivity) First, the proton conductive materials of samples No. 1 to No. 14 were subjected to cold isostatic pressing (3000 kgf / cm 2 ) to form a green compact, and then a test piece for measurement was prepared in accordance with JIS R1661 (Method of measuring electrical conductivity of fine ceramic ionic conductors).
[0051] Next, the initial proton conductivity of the test piece was measured at a temperature of 80° C. and a humidity of 80% RH by an AC impedance method using an impedance analyzer VMP-300 manufactured by Bio-logic.
[0052] Next, the test piece was left for an additional 100 hours in an environment of 80°C and 80% RH, and then the proton conductivity of the test piece after 100 hours at 80°C was measured by the AC impedance method using an impedance analyzer VMP-300 manufactured by Bio-logic.
[0053] The rate of decrease in proton conductivity is shown in Table 1. The rate of decrease in proton conductivity is the value obtained by dividing the initial proton conductivity by the proton conductivity after 100 hours.
[0054] In Table 1, the rate of decrease in proton conductivity was evaluated as ◎ (excellent) when it was 8% or less, as ○ (good) when it was more than 8% and 10% or less, and as × (unacceptable) when it was more than 10%.
[0055] [Table 1]
[0056] As shown in Table 1, the volume of pores with a diameter of 5 nm or less is set to 0.040 cm 3 In samples Nos. 2, 4, 5, 7, 9, 10, 12 to 14, in which the volume of pores with a pore diameter of 5 nm or less was 0.040 cm 3The decrease in proton conductivity was suppressed compared to samples Nos. 1, 3, 6, 8, and 11, which had a pore size of 5 nm or less and a volume of 0.040 cm 3 This is because the samples with a pore size of 5 nm or less were able to take in the moisture required for proton conduction by utilizing the capillary condensation phenomenon in fine pores with a pore size of 5 nm or less.
[0057] As shown in Table 1, the volume of pores with a diameter of 5 nm or less is set to 0.040 cm 3 / g or more, a treatment for forming pores with a diameter of 5 nm or less is required, whereas it was confirmed that the treatment method for forming pores with a diameter of 5 nm or less is not important.
[0058] Furthermore, as shown in Table 1, the volume of pores with a diameter of 5 nm or less is set to 0.056 cm 3 It was also found that by setting the proton conductivity at 0.1 to 1.0 μm / g or more, the rate of decrease in proton conductivity can be further suppressed. [Explanation of symbols]
[0059] 10 Sulfuric acid modified metal oxide particles 20 Metal Oxides 30 Sulfuric acid
Claims
1. The present invention is composed of a plurality of sulfate-modified metal oxide particles, each of which has a metal oxide containing at least one of Ti, Sn, Zr, and W, and a sulfuric acid supported on the surface of the metal oxide, In the pore size distribution curve obtained by the nitrogen adsorption method, the volume of pores with a pore size of 5 nm or less is 0.040 cm 3 / g or more, Proton conducting materials.
2. In the pore size distribution curve, the volume of pores having a pore size of 5 nm or less is 0.056 cm 3 / g or more, The proton conducting material of claim 1 .
Citation Information
Patent Citations
Proton conductive solid electrolyte and proton conductive solid electrolyte sheet
JP2002216537A
Proton-conductive material, film / electrode joint body, and fuel cell
JP2004158261A
Electrolyte film, production method of the same, and solid polymer fuel cell
JP2017036360A
Laminated electrolyte film, membrane-electrode assembly, water electrolysis cell, stack and water electrolysis apparatus
JP2018159121A
JPP7236519B
